A Retrospective on the Woodhouse Report: The Vision, the Performance and the Future - Palmer, Geoffrey (Victoria University of Wellington Law Review, 2019)
The following is a revised version of the second Woodhouse Memorial Lecture given at both the Victoria University of Wellington and the University of Auckland in September 2018. It traces the history and policy iterations of New Zealand's accident compensation scheme that flowed from the 1967 Woodhouse Report (the Report), a Royal Commission report chaired by Sir Owen Woodhouse. It discusses the features of the Report and the determination it showed to get rid of the common law action for damages for personal injury. It analyses the degree to which the Report was not followed in the journey it took through the political decision-making system. There is a critical analysis of the delivery of benefits, the administration of the scheme and its financing. The performance in accident prevention and rehabilitation is briefly covered. The method of settling disputes in the scheme has seen an unwelcome return to legalism. The lecture concludes with a strong plea to remove the anomalies created by the accident compensation scheme between the vicitims of accident who receive earnings related-benefit and those who are dealt with under the Social Security Act 2018 under which they receive flat rate benefits. The lecture concludes with some lessons for policymakers.